2020
DOI: 10.3390/pathogens9040290
|View full text |Cite
|
Sign up to set email alerts
|

Listeria monocytogenes Wall Teichoic Acid Glycosylation Promotes Surface Anchoring of Virulence Factors, Resistance to Antimicrobial Peptides, and Decreased Susceptibility to Antibiotics

Abstract: The cell wall of Listeria monocytogenes (Lm), a major intracellular foodborne bacterial pathogen, comprises a thick peptidoglycan layer that serves as a scaffold for glycopolymers such as wall teichoic acids (WTAs). WTAs contain non-essential sugar substituents whose absence prevents bacteriophage binding and impacts antigenicity, sensitivity to antimicrobials, and virulence. Here, we demonstrated, for the first time, the triple function of Lm WTA glycosylations in the following: (1) supporting the correct anc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…The resulting resistance to phage may contribute to the apparent FPE persistence of the ST321 and ST391 strains investigated here, which were closely related and recovered from the same FPE over more than two years. However, in addition to serving as phage receptors, WTA glycosylation is increasingly recognized for its importance in other functions including surface adhesion, biofilm formation, anchoring of virulence determinants to the cell surface and resistance to antimicrobial peptides [ 14 , 19 , 47 , 48 , 49 ]. It will be of interest to investigate such potential trade-offs with the strains investigated here and other FPE-derived phage-resistant strains of serotype 1/2a.…”
Section: Resultsmentioning
confidence: 99%
“…The resulting resistance to phage may contribute to the apparent FPE persistence of the ST321 and ST391 strains investigated here, which were closely related and recovered from the same FPE over more than two years. However, in addition to serving as phage receptors, WTA glycosylation is increasingly recognized for its importance in other functions including surface adhesion, biofilm formation, anchoring of virulence determinants to the cell surface and resistance to antimicrobial peptides [ 14 , 19 , 47 , 48 , 49 ]. It will be of interest to investigate such potential trade-offs with the strains investigated here and other FPE-derived phage-resistant strains of serotype 1/2a.…”
Section: Resultsmentioning
confidence: 99%
“…Taking into account our results, we wonder if the genes identified in VFDB (Figure 1 ) could provide the molecular basis to explain the pathogenic behaviour of the isolates of this work. Some of these genes have been reported in L. monocytogenes and other Gram‐positive bacteria, individually associated with roles in virulence and/or pathogenicity (Burkholder & Bhunia, 2010 ; Forster et al., 2011 ; Keeney et al., 2007 ; Meireles et al., 2020 ; Osanai et al., 2013 ; Rae et al., 2011 ; Réglier‐Poupet et al., 2003a,b ; Vázquez‐Boland et al., 2001 ). At least 5 of the 13 virulence genes found encode proteins related to bacterial adhesion to, and/or invasion into mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
“…The gtcA gene encodes an enzyme that catalyses teichoic acid glycosylation on L. monocytogenes wall. Proper glycosylation mediates key pathogenicity features: the correct anchoring of major surface virulence factors (Ami e InlB); resistance to antimicrobial peptides and decreased susceptibility to antibiotics (Meireles et al., 2020 ). The second gene present is prsA2 , which encodes a peptidyl prolyl cis‐trans isomerase that assists in correct protein folding.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported specific microbial resistance and their mechanisms against AMPs [117][118][119][120][121][122][123]. Pathogens can rapidly evolve and confer resistance to AMPs in vitro [124].…”
Section: Nanocarriers Of Ampsmentioning
confidence: 99%